Oral health knowledge, attitude and practices among health professionals in King Fahad Medical City, Riyadh - Mohammad Abdul Baseer; Mohammed Suliman Alenazy; Mohammad AlAsqah; Mansoor AlGabbani; Aleemullah Mehkari (Wolters Kluwer Medknow Publications, 2012)
Background: The aim of this study was to assess the oral health knowledge, attitude and practices among the health care professionals working at KFMC, Riyadh. Materials and Methods: A cross-sectional study of 161 health professionals consisting of doctors, nurses, pharmacists, technicians and medical students was carried out using a structured, self-administered, close-ended questionnaire. Responses were collected and descriptive statistics, ANOVA, Chi square tests and z-tests were performed. Results: Doctors showed a high mean knowledge score as compared with other health professionals. Comparison of oral health knowledge scores among the different types of health professionals yielded statistically significant differences (P < 0.05). The attitude toward visit to the dentist varied; 52.7% of nurses and 50% of technicians said that they would like to visit the dentist regularly. 66.7% of the medical students visit the dentist whenever they get pain in their tooth. 54.5% doctors and 45.8% pharmacists are likely to visit the dentist occasionally. For 60% medical students, tooth ache was the driving factor for their last visit. Majority of the health professionals said that the fear of drilling was the main reason for avoiding the dentist. Almost all the health professionals said that they cleaned their tooth by toothbrush and toothpaste. Less than 50% of the health professionals used mouth wash and dental floss. Less than 10% used Miswak and toothpick as part of their oral hygiene. Conclusion: Oral health knowledge among the health professionals working in KFMC, Riyadh was lower than what would be expected of these groups, which had higher literacy levels in health care, but they showed a positive attitude toward professional dental care.